Pengaruh Metode Sosiodrama pada Pembelajaran Aqidah Akhlak terhadap Perilaku Siswa Kelas VII MTSN 1 Kota Bogor - Izzah Hanifatul Hasanah; Oking Setia Priatna; Salati Asmahasanah (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Discussed research on the impact of method sosiodrama aqidah moral behavior in learning to students class VII of mtsn 1 bogor, research in quantitative methods used in descriptive where mtsn k1 bogor 1 as a research, research and object is vii students and teachers moral aqidah mtsn 1 bogor .Research show that influence own method in learning to aqidah sosiodrama moral behavior vii students having a correlation or influence being or class and is influence from the significant having been demonstrated by test the hypothesis t. Keywords: Method, Sosiodrama, Learning, Aqidah, Moral, Behavior, student